2020
DOI: 10.1021/acs.jafc.0c00586
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Phenolic Composition of Cork Stoppers from Different Geographical Origins

Abstract: Cork stopper granulates from five geographical origins from Portugal and six from Spain were analyzed regarding polyphenol composition by HPLC-DAD/ESI-MS and geographical discrimination studied by near-infrared spectroscopy (NIRS). The phenolic composition of the eleven origins ranged from 30 to 52 mg/g cork granulates, with vescavaloninic acid, castalagin, sanguisorbic acid dilactone, vescalagin, castavaloninic acid, dehydrated tergallic-C-Glc, and ellagic acid being the major compounds. NIRS revealed to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…37,49 PCA was performed to provide preliminary and visual approaches to find patterns of the variance of monoterpenes in the different samples, with projecting the original variables to smaller number of latent variables. 50 PCA was performed for the monoterpene profiles of the 24 samples analyzed (four developmental stages × two treatments × three biological replicates) (Figure 1B,D). The analysis indicated that the monoterpene profiles largely varied based on berry growth, with an obvious distinction between different stages, largely influenced by PC1.…”
Section: Resultsmentioning
confidence: 99%
“…37,49 PCA was performed to provide preliminary and visual approaches to find patterns of the variance of monoterpenes in the different samples, with projecting the original variables to smaller number of latent variables. 50 PCA was performed for the monoterpene profiles of the 24 samples analyzed (four developmental stages × two treatments × three biological replicates) (Figure 1B,D). The analysis indicated that the monoterpene profiles largely varied based on berry growth, with an obvious distinction between different stages, largely influenced by PC1.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of cork is highly variable and is affected by diverse factors including age of tree, geographical origin and climate. [27][28][29] Thus, the as-received cork was subjected to an extensive component analysis, details of which are provided in the methods section. The major components of cork can be categorized into four, namely extractives, suberin, polysaccharides and lignin.…”
Section: A Characterization Of As-received Corkmentioning
confidence: 99%
“…The characteristics of the two main chemical components (suberin and lignin, which represent 53% and 26%, respectively, of the cell wall) are responsible for the unique characteristics of cork: impermeability to fluids, low density, buoyancy, low thermal coefficient, high elasticity and deformation behaviour without fracturing if compressed, and long durability [ 5 ]. However, cork composition varies with geographic origin, climate, soil conditions, genetic origin, tree dimensions, age (virgin or reproduction), and growth conditions [ 27 , 28 ]. Recently, it has been described that the variability associated with the tree is much more relevant than the effect of the scarcity of water.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS technique showed to be a powerful tool to discriminate origins and predict the concentration of polyphenols. However, the variability in the phenolic compound composition of cork samples was high, and it was not influenced by geographical location [ 27 ]. Within the same regions, Guedes de Pinho et al [ 28 ] demonstrated three main clusters of regions according to their chemical similarity; however, geographical proximity was not found [ 28 ].…”
Section: Introductionmentioning
confidence: 99%